Comparisons of the Serum Osteopontin Levels of Patients with Dipper and Non-Dipper Hypertension - Kucukukur, Murat; Akbulut, Mehmet (My University, 2024)
Hypertension (HT) is a preventable significant cause of morbidity and mortality that affects millions of people worldwide. Inflammation plays an important role in the pathophysiology of cardiovascular diseases (CVD) and non-dipper hypertension (NDHT). Hypertension has a circadian rhythm. The aim of this study was to examine the difference in the levels of osteopontin (OPN), an inflammatory mediator, between the DHT and NDHT groups. Materials and Methods: Patients with hypertension who admitted to the cardiology outpatient clinic were evaluated in this cross-sectional study. HT was defined as systolic blood pressure (SBP) ?140 mmHg and/or diastolic blood pressure (DBP) ?90 mmHg, or the patient receiving anti-hypertensive treatment. A 24-hour ambulatory blood pressure monitoring was performed for participats then patients were separated into two groups according to their results as DHT and NDHT. All the patients underwent echocardiography, and serum OPN level was measured with the ELISA method. Results: We enrolled 40 DHT and 40 NHDT patients in this study. Serum OPN levels were significantly different between two groups (NDHT=215.50±114.44, DHT=152.12±92.76, p=0.008). The left ventricle mass index and left atrium diameter were significantly higher in NDHT group compared to DHT group (IVS; NDHT=11.60±1.24, DHT=10.30±1.55 p<0.001 LV Mass; NDHT=175.35±40.75, DHT=159.36±36.32 p<0.001, LA; NDHT=37.90±3.90, DHT=33.55±3.32 p<0.001). The total cholesterol level was found to be significantly higher in the NDHT group than in the DHT group (NDHT=209.15±28.24, DHT=189.72±33.25 p=0.006). Conclusion: Our study showed that serum OPN levels were higher in the NDHT group than in the DHT group.
Keywords: Inflammation; hypertension; osteopontin; Dipper; non dipper